A critical discussion on issues of higher education: Curriculum internationalization, challenges, and opportunities - Evangelia Fragouli (Association for Scientific Computing Electrical and Engineering(ASCEE), 2020)
Through the application of literature review and review of the higher education framework for internationalization, the present work presents a critical reflection of the challenges addressed in order for a curriculum in higher education to be internationalized and provides a practical guide regarding the required steps that need to be followed. A literature research approach is applied as a methodological approach, and the example of internationalizing a business management curriculum is used as a case for this study and the key research questions addresses what assist educational leaders and educational decision-makers to understand what is important to be considered when they plan, organize, design and implement activities for internationalizing a curriculum. The study also challenges that a more comprehensive framework is needed towards internationalization, and through reflection upon personal experience, provides practical guidance and recommendations to academics and educators on how higher education curricula can become international in context and practice.